Physician‐reported barriers to referring cancer patients to specialists: Prevalence, factors, and association with career satisfaction. Issue 1 (5th September 2014) - Kwon, Daniel H.; Tisnado, Diana M.; Keating, Nancy L.; Klabunde, Carrie N.; Adams, John L.; Rastegar, Afshin; Hornbrook, Mark C.; Kahn, Katherine L.
<x xml:space="preserve">Abstract</x> BACKGROUND Quality care for patients with cancer often requires access to specialty providers, but little is known about barriers to referring cancer patients for specialized care. Referral barriers may also lessen physician career satisfaction. The study was aimed at determining what factors are associated with these barriers and whether greater barriers are associated with low career satisfaction. METHODS This cross‐sectional study examined 1562 primary care physicians (PCPs) and 2144 specialists responding to the multiregional Cancer Care Outcomes Research and Surveillance Consortium physician survey. The prevalence of physician‐reported barriers to referring cancer patients for more specialized care (restricted provider networks, preauthorization requirements, patient inability to pay, lack of surgical subspecialists, and excessive patient travel time) was assessed. The 5 items were averaged to calculate a barrier score. A multivariate linear regression was used to determine physician and practice setting characteristics associated with the barrier score, and a multivariate logistic regression was used to analyze the association of the barrier score with physician career satisfaction. RESULTS Three in 5 physicians reported always, usually, or sometimes encountering any barrier to cancer patient specialty referrals. In adjusted analyses of PCPs and specialists, international medical graduates, physicians practicing in solo or government‐owned practices, and physicians with <90% of their patients in managed care plans had higher barrier scores than others (P < .05). High barrier scores were associated with lower physician career satisfaction among PCPs and specialists (P < .05). CONCLUSIONS Many physicians experience barriers to specialty referral for cancer patients. Uniform systems for providing and tracking timely referrals may enhance care and promote physician career satisfaction. Cancer 2015;121:113–122. © 2014 American Cancer Society.